Ethosomes as Promising Novel Transdermal Drug Delivery System and their Therapeutic Applications – A Review - S. Nirmala, (Asian Journal of Pharmaceutics (AJP), 2025)
Inadequate penetration of therapeutically active chemicals is the main factor affecting transdermal drug delivery system networks. The stratum corneum (SC) serves as the skin’s initial line of defense against drug molecule penetration. To date, this field has employed a number of tactics to overcome the SC barrier limits. The main purpose of a few innovative methods, including as liposomes, niosomes, ethosomes, and transfersomes, is to make pharmaceutical and cosmetic substances more permeable through the SC barrier. The melting point of SC lipids is lowered by ethosomes, which are stable, elastic, nanoscale vesicles with high phospholipid and ethanol content that interact with the polar head domain of lipid molecules. Finally, it increases lipid fluidity and cell membrane permeability. This section provides an overview of the most recent ethosome updates, depending on several pharmacological dose forms, involving gels, patches, and creams. There is also a brief discussion on updated ethosome patents. To sum up, ethosomes are an ideal vehicle for the delivery of drugs, cosmetics, and other substances and can be used in place of traditional pharmaceutical applications.